2022
DOI: 10.3389/fpsyg.2022.689815
|View full text |Cite
|
Sign up to set email alerts
|

Gender Norms and Gender Equality in Full-Time Employment and Health: A 97-Country Analysis of the World Values Survey

Abstract: BackgroundAlmost nowhere in the world do women participate as much as men in the labor force. Despite differences in countries’ economic, social and cultural contexts, gender norms—unwritten rules of acceptable actions for men and women—have been found to affect women’s labor participation across contexts. Gender norms include those regulating who takes care of children, who is expected to earn more, and in which sectors men and women should work. Importantly, norms affect access to labor markets at times of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…In several other low-and middle-income countries such as Yemen, Iraq, and Bahrain, the percentage of proequality cultural norms was less than 20% (Cislaghi et al, 2022). These findings are consistent with our results as we found that 28.6% of respondents from Afghanistan scored strongly disagree and 32.8% scored disagree with the question that female employees get the same opportunities as male employees.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In several other low-and middle-income countries such as Yemen, Iraq, and Bahrain, the percentage of proequality cultural norms was less than 20% (Cislaghi et al, 2022). These findings are consistent with our results as we found that 28.6% of respondents from Afghanistan scored strongly disagree and 32.8% scored disagree with the question that female employees get the same opportunities as male employees.…”
Section: Discussionsupporting
confidence: 91%
“…In five European countries (Iceland, Denmark, Sweden, Norway, and Andorra), pro-equality percentages were demonstrated by more than 90% of the countries surveyed. However, in 14 countries, the pro-equality percentage was held by less than 20% of the individuals surveyed (Cislaghi et al, 2022). See Figure 3 In developing countries such as Afghanistan, girls with a lower level of literacy spend more time performing unpaid domestic jobs than boys (Seedat & Rondon, 2021).…”
Section: Employmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the gender distribution, except for articles whose inclusion criteria were “men only” [ 34 ] or “women only” [ 35 ], there was a clear predominance of women in the distributions. Although the female population in the health sector is larger than the male population (women represented 70% of the health and social work workforce) [ 54 ], the scientific literature is deficient in a real analysis of women’s participation in full-time employment (excluding the role of full-time caregivers without job recognition) [ 55 ]. By the same token, one-third of the reviewed articles did not report data disaggregated by gender, because user behaviour was analysed anonymously in the comments section of social networks, which did not allow researchers to know the gender of the users being evaluated.…”
Section: Discussionmentioning
confidence: 99%